Student Worksheets with Scientific Literacy Oriented on Hydrolysis Matter by Utilizing Surrounding Materials as an Alternative Practicum in Pandemic Era - Putri, Gayatri Rajadewi Mega; Mitarlis, Mitarlis (FKIP-Universitas Riau, 2021)
Student worksheets are needed to support the learning process that improves student's scientific literacy ability. This study aims to determine the feasibility of student worksheets with science literacy oriented on hydrolysis matter by utilizing surrounding materials as an alternative practicum activity in pandemic era. Research design was used the 4-D model limited to the developing stage with nine students of senior High School as research subjects. The student worksheet's feasibility is viewed from three aspects: validity, practicality, and effectiveness. The student worksheets that developed is feasible if it gets ≥ 61% on the validity and practicality aspects and the N-gain is ≥ 0.3 for the effectiveness aspect. In the validity aspect, the score was 97.20% and 97.00% for the content and construct validity criteria, on very good category. Practicality is viewed from the student response questionnaire results that get an average percentage of 97% and it’s supported by the results of student’s activity observations that get an average percentage of 92.84% on very practical category. The effectiveness aspect in improving science literacy ability indicated by the N-gain score average of 0.88, which is in the high category. Thus the student worksheets developed is feasible for use in the learning process.